Relationships between metabolic markers and obesity measures in two populations that differ in stature - The SAMINOR Study - Michalsen, Vilde Lehne; Braaten, Tonje; Kvaløy, Kirsti; Melhus, Marita; Broderstad, Ann Ragnhild (Obesity Science & Practice, 2020)
Background - The relationships between metabolic markers and obesity measures may differ by ethnicity, sex, and height. Questions have been posed whether these relationships differ by ethnicity in the population in Northern Norway, but this has not been explored yet. Objectives - Investigate the relationships between metabolic markers and obesity measures in Sami and non‐Sami and explore the impact of stature. Methods - In total, 13 921 men and women aged 30 and 36 to 79 years (22.0% Sami) from a population‐based cross‐sectional survey in Norway, the SAMINOR 1 Survey (2003‐2004, 57.2% attendance), were included. Relationships between triglycerides, high‐density lipoprotein cholesterol, glucose, systolic/diastolic blood pressure (BP), metabolic syndrome and diabetes mellitus as outcomes, and body mass index (BMI), waist circumference (WC), and waist‐to‐height ratio (WHtR), respectively, were modelled using fractional polynomial regression. Appropriate interaction analyses and adjustments were made. Results - The non‐Sami were approximately 6 cm taller than the Sami. No interactions were found between ethnicity and obesity. At the same levels of WC, BMI, or WHtR, levels of lipids and BP differed marginally between Sami and non‐Sami, but these were eliminated by height adjustment, with one exception: At any given WC, BMI, or WHtR, Sami had approximately 1.4 mmHg (95% CI, −2.1 to −0.7) lower systolic BP than non‐Sami ( P values < .001). Conclusions - Height explained the marginal ethnic differences in metabolic markers at the same level of obesity, except for systolic BP, which was lower in Sami than in non‐Sami at any given BMI, WC, or WHtR.